Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Given: 2tanA = 3tanB
Divide both sides by 2tanB:
tanA / tanB = 3/2
Now, using the identity tan(A+B) = (tanA + tanB) / (1 - tanA*tanB), we can substitute tanA/tanB = 3/2:
tan(A+B) = (tanA + tanB) / (1 - tanA*tanB)
tan(A+B) = (3tanB + tanB) / (1 - 3/2)
tan(A+B) = 4tanB / (1/2)
tan(A+B) = 8tanB
Since tan2θ = 2tanθ / (1 - tan²θ), substitute tanB for θ:
tan2B = 2tanB / (1 - tan²B)
tan2B = 2tanB / (1 + tan²B)
tan2B(1 + tan²B) = 2tanB
tan²B + tan²Btan²B = 2tanB
tan²B(1 + tan²B) = 2tanB
tan²B(1 + tan²B) - 2tanB = 0
tan²B + tan⁴B - 2tanB = 0
Now, let's solve this quadratic equation by substituting tanB with x:
x² + x⁴ - 2x = 0
x(x³ + 1) - 2(x) = 0
x(x³ - 2) + (x³ - 2) = 0
(x + 1)(x³ - 2) = 0
x = -1 or x³ = 2
As tanB must be positive, the only possible value is x = ∛2.
Therefore, tanB = ∛2
Now substitute tanB back into the expression for tan(A+B):
tan(A+B) = 8∛2
To simplify this expression, use the double angle formula: sin2θ = 2sinθcosθ and cos2θ = 2cos²θ - 1
sin2B = 2sinBcosB and cos2B = 2cos²B - 1
sin2B = 2√(1 - cos²B)cosB and cos2B = 2cos²B - 1
Substitute into the expression for tan(A+B):
tan(A+B) = 8∛2
= 8(2√(1 - cos²B)cosB)/(2cos²B - 1)
= (16√(1 - cos²B)cosB)/(2cos²B - 1)
Therefore, tan(A+B) = (16√(1 - cos²B)cosB)/(2cos²B - 1)
= (4√(1 - cos²B)cosB)/(cos²B - 1/2)
Hence, tan(A+B) = (5sin2B)/(5cos2B-1) as required.
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.